Pengaruh Ukuran Pemberian Nafkah Keluarga Dalam Mewujudkan Keluarga Yang Harmonis - Wijaya, Jufri Aldhi; Shinwanuddin, M. (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2025)
Marriage is a method chosen by God as the way for man to live. Maintaining the permanence of a marriage in harmony, full of love and affection is not easy. Because inmarriage there are rights and obligations that must be fulfilled each between husband and wife. Among the obligations of the husband is to provide for the wife, that is, all the needs and necessities that apply according to circumstances and places, such as food, clothing, home and so on. The study and discussion of this thesis is how the level of provision of income according to the people of Bancong Village, Wonoasri District, Madiun Regency, how household harmony according to the people of Bancong Village, Wonoasri District, Madiun Regency and how the relevance of the level of providing income to household harmony in the community of Bancong Village, Wonoasri District, Madiun Regency. The type of research used by the author in this thesis is field research. While the approach used in this study is qualitative. This research is descriptive. In data collection researchers use interview, observation and documentation methods. Data analysis techniques use data reduction, data presentation and conclusion drawing / verification. The results of this study show that in the opinion of the people of Bancong Village, Wonoasri District, Madiun Regency, the rate of providing is the size or size of the income given by the husband to the wife each month and cannot be determined the amount each month because it depends on the income obtained by the husband in that month and who regulates family needs is the wife while the husband has the obligation to earn a living to meet the needs family. While a harmonious household is the provision of overall husband affection to the whole family and the balance between the rights and obligations of married couples so that the family is always in peace and peace without any gaps between one another. Meanwhile, regarding the relevance of the level of provision according to the people of Bancong Village, Wonoasri District, Madiun Regency is that it cannot have an influence because the local community does not really mind the rules on the rate or size of bread, the most important thing is that the provision can meet the needs of the family.